Ectrodactyly–Ectodermal Dysplasia–Cleft Lip/Palate Syndrome – Variable Presentation among First-degree Relatives of a Family - Shivani Ranjan; Neha Akhoon (Indian Journal of Paediatric Dermatology)
Ectrodactyly–ectodermal dysplasia–cleft lip/palate (EEC) syndrome is a rare genetic disorder that affects ectodermal derived structures, including teeth, nails, hair, and sweat glands along with ectrodactyly and clefting of lip/palate. This case series presents autosomal dominant transmission of EEC syndrome in a family and highlights the intrafamilial variations indicating variable penetrance.